All gene-sized DNA molecules in four species of hypotrichs have the same terminal sequence and an unusual 3' terminus. - Klobutcher, L A (1981)
In hypotrichous ciliates, all of the macronuclear DNA is in the form of low molecular weight molecules with an average size of approximately 2200 base pairs. Total macronuclear DNA from four hypotrichs has been shown to have inverted terminal repeats by direct sequence analysis. In Oxytricha nova, Oxytricha sp., and Stylonychia pustulata, this terminal sequence may be written as 5'-C4A4C4A4C4 ... 3'-G4T4G4T4G4T4G4T4G4 ... In Euplotes aediculatus, the sequences is similar but differs in the lengths of the duplex region (28 base pairs) and of the putative 3' extension (14 base pairs). Also in Euplotes, a second common sequence of 5 base pairs (A-A-C-T-T-T-T-G-A-A) occurs internal to the terminal repeat and a 17-base-pair heterogeneous region: 5'-C4A4C4A4C4A4C4(X)17T-T-G-A-A ... 3'-G2T4G4T4G4T4G4T4G4T4G4(X)17A-A-C-T-T ... The length of the terminal repeat sequence for O. nova was confirmed in cloned macronuclear DNA molecules.